Agricultural technologies and tropical deforestation - Angelsen, A.; Kaimowitz, D. (CAB International, 2001)
Do improvements in agricultural technology protect or endanger tropical forests? This book examines this controversial issue. It includes both theoretical frameworks for analysing the issue as well as case studies covering a wide range of geographical regions, technologies, market conditions and types of agricultural procedures. The authors identify technologies, contexts and policies that are likely to be beneficial to both farmers and forests. In this way the book provides concrete guidance to international aid agencies, agricultural research and technology transfer programmes, conservation projects and forestry organizations. This book contains 22 chapters: introduction and overviews, papers and case studies from developed countries, Latin America, Africa, Asia, and summaries. It is suitable for those working and researching in the areas of forestry, tropical agriculture and development economics and policy.